Implementation of Soft Starter on Pumps and Agricultural Monitoring Systems with Pest Exercise Technology to Increase Agricultural Efficiency - Raafi’u, Brian; Fauzi, Eko Rian; Adhim, Fauzi Imaduddin (Universitas Nahdlatul Ulama Surabaya, 2023)
The pump starting current can be up to 500% to 800% higher than normal current. Besides raising the electricity bill, a very high current surge at starting can cause damage to other electronic components. This study aims to implement a soft starter that functions to reduce the electrical power required to start the pump up. To measure electrical variables while the pump is working, the PZEM-004t sensor is used as a voltage, current, and energy sensor. The sensor has been validated and has an accuracy of 99.63% for current measures and 99.87% for voltage measures. In addition, to increase the efficiency of agricultural yields, a monitoring system for soil moisture in the fields is also applied with pest control technology. The soil moisture sensor YL-69, which has been validated with an accuracy of 98.27% is used to measure soil moisture in agricultural land. Specifically, this monitoring system utilizes solar electricity, which is abundant in open areas, while the pump system still uses grid electricity. Those two systems are then integrated using an android application. The results of this study found that the use of a soft starter can reduce current up to 20.64% with a 3A motor and 15.32% with a 1.7A motor.